Single‐cell sequencing maps gene expression to mutational phylogenies in PDGF‐ and EGF‐driven gliomas. Issue 11 (25th November 2016) - Müller, Sören; Liu, Siyuan John; Di Lullo, Elizabeth; Malatesta, Martina; Pollen, Alex A; Nowakowski, Tomasz J; Kohanbash, Gary; Aghi, Manish; Kriegstein, Arnold R; Lim, Daniel A; Diaz, Aaron
Abstract: Glioblastoma multiforme (GBM) is the most common and aggressive type of primary brain tumor. Epidermal growth factor (EGF) and platelet‐derived growth factor (PDGF) receptors are frequently amplified and/or possess gain‐of‐function mutations in GBM. However, clinical trials of tyrosine‐kinase inhibitors have shown disappointing efficacy, in part due to intra‐tumor heterogeneity. To assess the effect of clonal heterogeneity on gene expression, we derived an approach to map single‐cell expression profiles to sequentially acquired mutations identified from exome sequencing. Using 288 single cells, we constructed high‐resolution phylogenies of EGF‐driven and PDGF‐driven GBMs, modeling transcriptional kinetics during tumor evolution. Descending the phylogenetic tree of a PDGF‐driven tumor corresponded to a progressive induction of an oligodendrocyte progenitor‐like cell type, expressing pro‐angiogenic factors. In contrast, phylogenetic analysis of an EGFR ‐amplified tumor showed an up‐regulation of pro‐invasive genes. An in‐frame deletion in a specific dimerization domain of PDGF receptor correlates with an up‐regulation of growth pathways in a proneural GBM and enhances proliferation when ectopically expressed in glioma cell lines. In‐frame deletions in this domain are frequent in public GBM data. Synopsis: An approach is presented for mapping single‐cell expression profiles to sequentially acquired mutations identified by exome sequencing. Phylogenies of EGF‐driven and PDGF‐driven gliomas are constructed, modeling transcriptional kinetics during tumor evolution. Single‐cell RNA‐seq and integrated exome‐seq of glioblastoma biopsies map gene expression to mutational structure. Descending the phylogenetic tree of a proneural, PDGF‐driven glioblastoma multiforme (GBM) corresponds to a progressive induction of an oligodendrocyte progenitor‐like cell type from a neural stem cell‐like precursor. An in‐frame deletion in a PDGF‐receptor dimerization domain correlates with up‐regulation of growth pathways in vivo and enhances proliferation in vitro . In‐frame deletions in a PDGF‐receptor dimerization domain are frequent events in TCGA data. Abstract : An approach is presented for mapping single‐cell expression profiles to sequentially acquired mutations identified by exome sequencing. Phylogenies of EGF‐driven and PDGF‐driven gliomas are constructed, modeling transcriptional kinetics during tumor evolution.